Knowledge, Beliefs and Attitudes of Turkish Patients on In-Center Hemodialysis Toward Home Hemodialysis: A Pilot Study - Belgüzar Kara; İlknur Yazıcıoğlu (Journal of Clinical and Practical Nursing, 2018)
This pilot study aimed to determine the knowledge, beliefs and attitudes of Turkishpatients on in-center hemodialysis about home hemodialysis (HHD) and their related factors. A cross-sectional study was performed among 32 patients on in-center hemodialysis in a tertiary hospital in Turkey. Data were collected by using a questionnaire form including sociodemographic and disease-related characteristics and knowledge, beliefs and attitudes about HHD. Data analysis were performed using descriptive statistics and the Chi-square test. While the majority of the patients (65.6%) reported having knowledge about HHD, only 34.4% of them had ever considered it. The most common perceived benefits of HHD were minimized wasted time (71.9%) and more time spent with family (71.9%). The most common perceived barrier to HHD was also housing constraints (90.6%). The results of this study highlight the importance of recognizing knowledge, beliefs and attitudes toward HHD in patients on in-center hemodialysis for increasing the use of the treatment.
Keywords: attitudes